ANALISIS PENEMPATAN REGULATOR SECTOR JARINGAN GAS RUMAH TANGGA BERDASARKAN MAXIMUM COVERAGE LOCATION PROBLEM (CASE STUDY: JARINGAN GAS RUMAH TANGGA KOTA DEPOK, JAWA BARAT) - Angel Olivia; Harummi Sekar; Mirna Lusiani (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
This research is about the household gas network and the purpose is to find out the optimal number and location of the regulator sectors for 6 urban villages in Depok. The problem is solved using Maximum Coverage Location Problem to get the minimum amount of facility with the distance limit of 500 meters. The tool used in this research is AMPL to get optimal solution of the problem. In validating the model, calculations are done using small instances for each urban villages and it resulted that Beji only needs 6 facilities for serve all consumers. The calculation using large instances resulted that number facilities needed to serve 7.515 consumers is 12 from the 19 available facilities. The facilities used are RS B 001, RS B 006, RS B 007, RS B 009, RS BT 01, RS BT 02, RS BT 03, RS BT 04, RS 01, RS 02, RS 04 and RS 06. This means that the available facilities exceed the facilities are be used to serve consumers. This research is expected to assist the development of household gas networks in Indonesia, especially in Depok by increasing the consumers around existing regulator sectors.